Oral and Cervicofacial Infection Secondary to Agranulocytosis Caused by Antithyroid Medication: A Case Report - Paredes Vilchez, Renzo Angel (2023)
Agranulocytosis refers to a low white blood cell count, specifically neutrophils, which can be caused by certain medications such as antithyroid drugs (ATD). This condition can result in oral manifestations, including diffuse gingival ulceration or necrosis. We present the case of a 26-year-old female patient with a history of hyperthyroidism who came to the emergency department of Alberto Sabogal Sologuren National Hospital with swelling on the left side of her face, accompanied by dysphagia, multiple ulcerated lesions in the oral mucosa involving bone tissue, as well as fever and general malaise. After conducting additional tests, the patient was diagnosed with oral and cervicofacial infection secondary to agranulocytosis caused by methimazole treatment. While the global literature reports cases of agranulocytosis as an adverse effect of antithyroid medication, with documented oral manifestations, only a few cases demonstrate cervical involvement. Therefore, we present this uncommon case from diagnosis to treatment.